N-(3,4-Dimethylphenyl)-2,4-dimethylbenzenesulfonamide - Gowda, B. Thimme (International Union of Crystallography, 2010)
In the title compound, C(16)H(19)NO(2)S, the dihedral angle between the aromatic rings is 47.2 (2)°. The crystal structure features zigzag C(4) chains linked by N—H⋯O hydrogen bonds.